Ficolin‐1 gene (FCN1) −144 C/A polymorphism is associated with adverse outcome of severe pneumonia in the under‐five Egyptian children: A multicenter study. Issue 5 (6th March 2020) - Elkoumi, Mohamed A.; Abdellatif, Sawsan H.; Mohamed, Faisal Y.; Sherif, Ahmed H.; Elashkar, Shaimaa S. A.; Saleh, Rabab M.; Boraey, Naglaa F.; Abdelaal, NourEldin M.; Akeel, Nagwa E.; Elhewala, Ahmed A.; Mosbah, Amira A.; Zakaria, Mervat T.; et al.
Abstract: Background: Pneumonia is the foremost cause of child death worldwide. M‐ficolin is encoded by the FCN1 gene and represents a novel link between innate and adaptive immunity. Objectives: To investigate the FCN1 −144 C/A (rs10117466) polymorphism as a potential marker for pneumonia severity and adverse outcome namely complications or mortality in the under‐five Egyptian children. Methods: This was a prospective multicenter study that included 620 children hospitalized with World Health Organization‐defined severe pneumonia and 620 matched healthy control children. Polymorphism rs10117466 of the FCN1 gene promoter was analyzed by PCR‐SSP, while serum M‐ficolin levels were assessed by ELISA . Results: The FCN1 A/A genotype and A allele at the −144 position were more frequently observed in patients compared to the control children (43.4% vs 27.6%; odds ratio [OR]: 1.62; [95% confidence interval CI: 1.18‐2.2]; for the A/A genotype) and (60.8% vs 52.5%; OR: 1.4; [95% CI: 1.19‐1.65]; for the A allele); P < .01. The FCN1 −144 A/A homozygous patients had significantly higher serum M‐ficolin concentrations (mean: 1844 ± 396 ng/mL) compared with those carrying the C/C or C/A genotype (mean: 857 ± 278 and 1073 ± 323 ng/mL, respectively; P = .002). FCN1 −144 A/A genotype was an independent risk factor for adverse outcomes in children with severe pneumonia (adjusted OR = 4.85, [95% CI: 2.96‐10.25]; P = .01). Conclusion: The FCN1 A/A genotype at the −144 position was associated with high M‐ficolin serum levels and possibly contributes to enhanced inflammatory response resulting in the adverse outcome of pneumonia in the under‐five Egyptian children.